The GeoCitizen-approach: community-based spatial planning – an Ecuadorian case study - Atzmanstorfer, Karl; Resl, Richard; Eitzinger, Anton; Izurieta, Xiomara (Informa UK Limited, 2014)
Over the last years, geospatial web platforms, social media, and volunteered geographic information (VGI) have opened a window of opportunity for traditional Public Participatory GIS (PPGIS) to usher in a new era. Taking advantage of these technological achievements, this paper presents a new approach for a citizen-orientated framework of spatial planning that aims at integrating participatory community work into existing decision-making structures. One major cornerstone of the presented approach is the application of a social geoweb platform (the GeoCitizen platform) that combines geo-web technologies and social media in one single tool allowing citizens to collaboratively report observations, discuss ideas, solve, and monitor problems in their living environment at a local level. This paper gives an account of an ongoing participatory land-zoning process in the Capital District of Quito, Ecuador, where the GeoCitizen platform is applied in a long-term study.